2007
DOI: 10.1080/14786410600905907
|View full text |Cite
|
Sign up to set email alerts
|

Constituents ofGardenia volkensii: their brine shrimp lethality and DPPH radical scavenging properties

Abstract: The seeds and the pulp of Gardenia volkensii yielded one new iridiod, namely 4-(2N-gardenamide)n-butanoic acid, together with the known iridoids genipin and genipin gentiobioside, the pterocarpin medicarpin, coumarins, phenylpropanoids, benzenoids and triterpenes. The structures of these were determined on the basis of spectroscopic data and by comparison of obtained data with those from literature. The fruit extracts of this plant exhibited moderate radical scavenging activity against DPPH radical and moderat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 10 publications
2
13
0
Order By: Relevance
“…However, the ethanol-based GJE extract was significantly less effective than was BHT (P < 0.05; Table 2) but showed stronger scavenging activity than those of some common fruits studied by Yan, Teng, and Jhi (2006). In addition, the fruit extract of Gardenia volkensii also exhibited moderate DPPH radical-scavenging activity, as reported by Jumaa and Majindaa (2007). Furthermore, DPPH Å -scavenging activity was highly correlated with phenolic and flavonoid contents (r 2 = 0.9988 and 0.9816 for water extract and r 2 = 0.9989 and 0.998 for ethanol extract, respectively).…”
Section: Resultssupporting
confidence: 65%
“…However, the ethanol-based GJE extract was significantly less effective than was BHT (P < 0.05; Table 2) but showed stronger scavenging activity than those of some common fruits studied by Yan, Teng, and Jhi (2006). In addition, the fruit extract of Gardenia volkensii also exhibited moderate DPPH radical-scavenging activity, as reported by Jumaa and Majindaa (2007). Furthermore, DPPH Å -scavenging activity was highly correlated with phenolic and flavonoid contents (r 2 = 0.9988 and 0.9816 for water extract and r 2 = 0.9989 and 0.998 for ethanol extract, respectively).…”
Section: Resultssupporting
confidence: 65%
“…have reported that samples extracted from peeled quince showed a higher radical scavenging capacity than those extracted from pulped quince. Juma and Majinda have reported that gardenia showed a moderate level of DPPH scavenging activity, which is consistent with the results obtained for the whole fruit tea infusions in our study. We observed that there was a moderately positive correlation between samples and the DPPH scavenging capacity (r=0.534, p ≤0.05) in the case of the whole fruit infusions.…”
Section: Resultssupporting
confidence: 93%
“…Several studies substantiate the positive correlation of quality of phenolics with the DPPH free radical scavenging effect [32,33]. Although methanolic fruit extract of G. latifolia was significantly less effective than ascorbic acid but showed stronger scavenging activity than those of the fruit extracts of Gardenia volkensii [34] and Gardenia jasminoides [35]. From this study, it is imperative that the methanolic fruit extract of G. latifolia has showed significant antioxidant activity owing to the presence of phenolic compounds.…”
Section: In Vitro Antioxidant Activity Of G Latifolia Methanolic Frumentioning
confidence: 59%